Focus on the wonder years : challenges facing the American middle school - Juvonen, Jaana (Rand, 2004)
Young teens undergo multiple changes that seem to set them apart from other students. But do middle schools actually meet their special needs? The authors describe some of the challenges and offer ways to tackle them, such as reassessing the organization of grades K-12; specifically assisting the students most in need; finding ways to prevent disciplinary problems; and helping parents understand how they can help their children learn at home.